2022
DOI: 10.1200/op.21.00478
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients Placed in an Emergency Department Observation Unit of a Comprehensive Cancer Center

Abstract: PURPOSE Emergency department observation units (EDOUs) have been shown to decrease length of stay and improve cost effectiveness. Yet, compared with noncancer patients, patients with cancer are placed in EDOUs less often. In this study, we aimed to describe patients who were placed in a cancer center's EDOU to discern their clinical characteristics and outcomes. METHODS We performed a retrospective observational study that included all patients age 18 years and older who presented to our emergency department (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The low ED revisit and mortality rates in patients discharged from this EDOU after presenting with pain align with the overall low rate of adverse events experienced by all patients discharged from this EDOU. Interestingly, in a prior study, the ED revisit rate for patients discharged from this EDOU regardless of chief complaint was lower than that of patients discharged from its associated ED [ 13 ]. We also found that patients admitted to the hospital after their cancer pain was managed in an EDOU had a higher mortality rate compared to those who were discharged from the EDOU.…”
Section: Discussionmentioning
confidence: 99%
“…The low ED revisit and mortality rates in patients discharged from this EDOU after presenting with pain align with the overall low rate of adverse events experienced by all patients discharged from this EDOU. Interestingly, in a prior study, the ED revisit rate for patients discharged from this EDOU regardless of chief complaint was lower than that of patients discharged from its associated ED [ 13 ]. We also found that patients admitted to the hospital after their cancer pain was managed in an EDOU had a higher mortality rate compared to those who were discharged from the EDOU.…”
Section: Discussionmentioning
confidence: 99%
“…This unit is functional 24-hours a day and is staffed by an emergency or internal medicine physician along with advanced practice providers. Most patients who are placed in the observation unit originate from the ED; however, patients may also come directly from clinics or procedure areas (9). Additionally, patients may also be admitted directly to the hospital by their oncologists, while bypassing the ED.…”
Section: Study Settingmentioning
confidence: 99%
“…13 The inability to effectively manage pain worsens patients' quality of life and leads to greater health care utilization, especially emergency department (ED) visits. 5,14,15…”
Section: Introductionmentioning
confidence: 99%
“…13 The inability to effectively manage pain worsens patients' quality of life and leads to greater health care utilization, especially emergency department (ED) visits. 5,14,15 Almost half of patients with cancer visit the ED at least once within the first year after diagnosis, 16 and patients with cancer account for nearly four million annual ED visits in the United States. 17 Patients often present to the ED with symptoms (eg, pain, nausea/vomiting, and respiratory distress) or complications from cancer treatment (eg, neutropenia) or progression.…”
Section: Introductionmentioning
confidence: 99%